2011
DOI: 10.4061/2011/146927
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C-Induced Oxalate Nephropathy

Abstract: Although a multitude of syndromes have been thoroughly described as a result of vitamin deficiencies, over consumption of such substances may also be quite dangerous. Intratubular crystallization of calcium oxalate as a result of hyperoxaluria can cause acute renal failure. This type of renal failure is known as oxalate nephropathy. Hyperoxaluria occurs as a result of inherited enzymatic deficiencies known as primary hyperoxaluria or from exogenous sources known as secondary hyperoxaluria. Extensive literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 23 publications
2
56
1
2
Order By: Relevance
“…There are three recognized types of primary hyperoxaluria (PH): type 1 is due to defects in the gene that encodes the hepatic peroxisomal enzyme alanine glyoxylate aminotransferase (AGT); type 2 is due to defects in the gene that encodes the cytosolic enzyme glyoxylate reductase/hydroxypyruvate reductase (GRHPR); and type 3 is due to mutations in the uncharacterized gene DHDPSL. Secondary hyperoxaluria results from increased absorption in patients with intestinal malabsorption syndromes, direct dietary consumption of oxalate rich products, or ingestion of other substances (e.g., vitamin C), which may be metabolized into oxalate (7). …”
Section: Discussionmentioning
confidence: 99%
“…There are three recognized types of primary hyperoxaluria (PH): type 1 is due to defects in the gene that encodes the hepatic peroxisomal enzyme alanine glyoxylate aminotransferase (AGT); type 2 is due to defects in the gene that encodes the cytosolic enzyme glyoxylate reductase/hydroxypyruvate reductase (GRHPR); and type 3 is due to mutations in the uncharacterized gene DHDPSL. Secondary hyperoxaluria results from increased absorption in patients with intestinal malabsorption syndromes, direct dietary consumption of oxalate rich products, or ingestion of other substances (e.g., vitamin C), which may be metabolized into oxalate (7). …”
Section: Discussionmentioning
confidence: 99%
“…Failure of kidney function caused by the use of a sodium phosphate agent as colonoscopy preparation is well known . Even for the modest low‐volume method such as 2 L PEGA, there are unsolved concerns, which might be caused by excessive volume reduction by the preparation agent . Even though the present study had a relatively small sample size to fully estimate the risk of potential kidney injury, adverse outcome related to kidney was not encountered in any of the patients until the study completion date.…”
Section: Discussionmentioning
confidence: 78%
“…28 Even for the modest low-volume method such as 2 L PEGA, there are unsolved concerns, which might be caused by excessive volume reduction by the preparation agent. 8,27,29,30 Even though the present study had a relatively small sample size to fully estimate the risk of potential kidney injury, adverse outcome related to kidney was not encountered in any of the patients until the study completion date. Moreover, recent some studies demonstrated that the addition of adjuncts such as bisacodyl also has an additional benefit to achieve adequacy of bowel preparation.…”
Section: Discussionmentioning
confidence: 86%
“…Vitamin C, when administered in higher quantities into the human body, is reported to have caused kidney stones in some cases [32]. It is inferred that Vitamin C gets converted to oxalates [33]. But some study reported that the oxalate excretion is little related to the dietary intake [34].…”
Section: Food Habits With Stone Formationmentioning
confidence: 99%